Assemblage of filamentous fungi associated with aculeate hymenopteran brood in reed galls - Heneberg, Petr; Bizos, Jiří; Čmoková, Adéla; Kolařík, Miroslav; Astapenková, Alena; Bogusch, Petr (Journal of invertebrate pathology, 2016)
Monotypic stands of common reed and the reed-gall-associated insect assemblages are distributed worldwide. However, fungi associated with these assemblages have not been characterized in detail. Here we examined 5200 individuals (12 species) of immature aculeate hymenopterans or their parasitoids collected at 34 sampling sites in Central Europe. We noticed fungal outgrowth on exoskeletons of 83 (1.60%) larvae and pupae. The most common host was eudominant Pemphredon fabricii. However, the less abundant aculeate hymenopteran reed gall inquilines were infected at higher prevalence, these included Trypoxylon deceptorium, Trypoxylon minus, Hoplitis leucomelana and Hylaeus moricei (all considered new host records). We identified three fungal species, Penicillium buchwaldii (72% of cases), Aspergillus pseudoglaucus (22%) and Penicillium quebecense (6%). When multibrooded nests were affected, only a part of individuals was infected in 62% of cases. The sampling site-specific infection rate reached up to 13%, thus fungal infections should be considered an important variable driving the abundance of gall inquilines. Infections of generalist host species were more frequent than those of reed gall specialists, suggesting that suboptimal conditions decreased the immunocompetence of non-specialized species, which only occasionally nest in reed galls and feed in reed beds.
Keywords: Hymenoptera; Host-Pathogen Interactions; DNA, Fungal; fylogeneze; Aspergillus; Pupa; Phylogeny; nádory rostlin; DNA fungální; pravděpodobnostní funkce; kukla; Likelihood Functions; larva; Animals; interakce hostitele a patogenu; zvířata; Larva; Penicillium; Plant Tumors